Venezuelan migration a problem for Latin America? An analysis through history and its determinants - Peñafiel, Luis (2020)
This work analyzes how a government managed to gain total control of the State and put the Institutions to work not for the country but for it, and also seeks to identify what are the economic and non-economic determinants of Venezuelan migration between 1991-2018. For the generation of the model, the methodology of Ordinary Minimum Squares (MCO) is used. It is found that an increase in the Latin American GDP growth rate gap with respect to Venezuela generates an incentive to emigrate, in turn an increase in the gap between the participation rate of the average Latin American labor force with respect to Venezuela It causes more and more Venezuelans to decide to leave the country. Finally, a decrease in the mortality rate gap of less than five years in Latin America on average for Venezuela reaffirms the decision to seek better living conditions outside of Venezuela. This shows the great challenges that Latin American coordination will imply to counteract this issue that has become a humanitarian issue.